2021
DOI: 10.3389/fpsyt.2021.618805
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Regional Homogeneity in Melancholic and Non-melancholic Major Depressive Disorder at Rest

Abstract: Background: Melancholic depression has been viewed as one severe subtype of major depressive disorder (MDD). However, it is unclear whether melancholic depression has distinct changes in brain imaging. We aimed to explore specific or distinctive alterations in melancholic MDD and whether the alterations could be used to separate melancholic MDD from non-melancholic MDD or healthy controls.Materials and Methods: Thirty-one outpatients with melancholic MDD and thirty-three outpatients with non-melancholic MDD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 64 publications
2
21
1
Order By: Relevance
“…Orbitofrontal cortex plays an important role in decisionmaking, and decision-making impairment is associated with a susceptibility to suicidal symptoms (70), which is included in the cognitive disturbance. A previous study also reported the decreased ReHo in the right middle frontal gyrus was negatively correlated with depression symptoms in MDD patients (60). On the contrary with LOD patients, we found that the correlation between ReHo in the inferior frontal triangular gyrus and cognitive disturbance of EOD was positive (not significant).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Orbitofrontal cortex plays an important role in decisionmaking, and decision-making impairment is associated with a susceptibility to suicidal symptoms (70), which is included in the cognitive disturbance. A previous study also reported the decreased ReHo in the right middle frontal gyrus was negatively correlated with depression symptoms in MDD patients (60). On the contrary with LOD patients, we found that the correlation between ReHo in the inferior frontal triangular gyrus and cognitive disturbance of EOD was positive (not significant).…”
Section: Discussioncontrasting
confidence: 80%
“…The DLPFC dysfunction may be an early manifestation of MDD and that the right inferior frontal triangular gyrus plays an important role in the pathogenesis of the early stage of MDD; patients with mild DLPFC damage often appear to be uninterested in things, with slow thinking, poor memory, and lack of motivation (56)(57)(58)(59). Recently, one study using machine learning methods reported the abnormal ReHo in the left postcentral gyrus and right fusiform gyrus with a high accuracy for discriminating MDD from HC (60). These results and our study provide further evidence for the important role of the prefrontal lobe in MDD, which may help distinguish the depression subtypes for accurate diagnosis and treatment in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, computational and statistical models have been used to differentiate melancholic from nonmelancholic depression (9). The complexity and design of these models range from fundamental statistical analysis (10)(11)(12)(13) to machine learning models (14)(15)(16). In most of these studies, they analyzed neuroimaging data to identify the brain activities involved in melancholic depression (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The complexity and design of these models range from fundamental statistical analysis (10)(11)(12)(13) to machine learning models (14)(15)(16). In most of these studies, they analyzed neuroimaging data to identify the brain activities involved in melancholic depression (11)(12)(13)(14)(15)(16). In particular, they extracted functional connections from resting state functional MRI (rs-fMRI) data (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation